Green Serves the Dirtiest. On the Interaction between Black and Green Quotas - Christoph Böhringer; Knut Einar Rosendahl (Statistics Norway, Research Department, 2009)
Tradable black (CO2) and green (renewables) quotas gain in popularity and stringency within climate policies of many OECD countries. The overlapping regulation through both instruments, however, may have important adverse economic implications. Based on stylized theoretical analysis and substantiated with numerical model simulations for the German electricity market, we show that a green quota imposed on top of a black quota does not only induce substantial excess cost but serves the dirtiest power technologies as compared to a black quota regime only.
Keywords: D61; H21; H22; Q58; 330; Emissions Trading; Tradable Green Certificates; Overlapping Regulation